VoIP for dummies - Kelly, Timothy (Timothy V.) (--For dummies., 2005)
Put your phone system on your computer network and see the savingsSee how to get started with VoIP, how it works, and why it saves you moneyVoIP is techspeak for "voice over Internet protocol," but it could spell "saving big bucks" for your business! Here's where to get the scoop in plain English.